Factors Affecting Employee Retention of a State University in Eastern Visayas, Philippines (Global Journal of Management and Business Research, 2025)
Abstract- A low employee retention rate is incredibly disruptive to the growth of an organization The study examined the needs of employees of a State University in Eastern Visayas Philippines to remain in the organization for the maximum amount of time The study investigated the factors of employee retention of the said state university A survey was conducted using a structured questionnaire among 218 employees randomly selected from the two campuses of a State University Descriptive analysis was used to analyze the respondents sociodemographic characteristics employment profile retention awareness and willingness to stay in the university Binary logistics regression was employed to identify the factors affecting employee retention of a state university in Eastern Visayas Philippines Results showed that out of the eight sociodemographic variables examined only the employee s age significantly influenced job retention This implies that as the employee gets older he she will likely remain or stay in the university Regression results showed that workload work flexibility organizational culture and leadership were significant factors of employee retention
Keywords: factors; employee retention; state university; higher education; faculty; Philippines